Media text of convergent mass media in the context of discourse - Luschinskaya, Olga V. (Journal of the Belarusian State University. Journalism, 2019)
The article is focused on the notion of a media text which is considered within the discourse conception of convergent mass media functioning and represents a communicative product which includes both verbal (text representation of a message) and non-verbal (visual, illustrative material) components. It uses in its content elements of different ways and channels of information transmission – video and audio broadcast of content. The definitions of media discourse as well as its type – discourse of convergent mass media – are given. The latter is a special communicative phenomenon brought to life by a new informational surrounding, first of all, by the appearance of a web-platform. It is stated that in a media discourse its different types which reflect events, processes, ideas, knowledge, cultural realms of a separate society as well as of the whole world are crossed. These types of discourses are adapted in a media discourse according to the rules of functioning and are represented by means of the mass media language and extralinguistic parameters. The article also discusses specifics, characteristics and typology of a media text as the main notion of a media discourse. Attention is paid to such its property as creolization which means combination of verbal and non-verbal (pictorial, iconic) means of information transmission which together provide its integrity, coherence, completeness and achievement of a purpose stated by the author. Genre forms of a media text in convergent mass media are represented. These genre forms are distributed according to classification groups. Considered characteristics of a media text and its peculiarities of functioning in contemporary convergent mass media allow to conclude that a media text is not only a linear consequence of verbal signs but a semiotically complicated creolized multimedia product of communication which together with classical characteristics, functions and properties of a text acquires new qualities and formats as well as peculiarities of content. It is comprehended by the audience differently due to convergence.
Keywords: discourse; mass media discourse; discourse of convergent mass media; text; media text; creolization of a media text; comprehension of a multimedia product